CFD investigation of a natural ventilation wind tower system with solid tube banks heat recovery for mild-cold climate. (January 2022) - Liu, Miaomiao; Jimenez-Bescos, Carlos; Calautit, John
Abstract: Passive strategies are increasingly being employed in buildings to minimize their total energy consumption and emissions. Wind tower, a natural ventilation device, can capture the wind flow from higher locations and supply the air into the buildings' indoor space without consuming electric power. However, its use in mild-cold climate is limited due to excessive heat loss and thermal discomfort, in particular, during winter. Limited research has been conducted to explore the pre-heating of the supply air in the wind tower to address the issue and potentially increase its adoption in mild-cold climates. Therefore, a novel wind tower ventilation system integrated with solid tube banks heat recovery (HR) is proposed in this research. By combining with a passive heat recovery device, a wind tower can be operated under winter conditions to improve indoor ventilation while reducing the building heating energy consumption. A three-dimensional computational fluid dynamics (CFD) model was developed to investigate the effects of the longitudinal pitch (SL) and the transverse pitch (ST) of the HR device on the ventilation and thermal performance. The overall performance of the wind tower was evaluated under different outdoor wind speeds. The results show that the heat recovery can be improved by reducing SL and ST, raising the supply fresh air temperature by up to 6.4 °C. Furthermore, the proposed wind tower can provide sufficient ventilation for a typical classroom occupied by 15 people when the external wind speed exceeds 3 m/s. Highlights: Integrated solid tube heat recovery device into a four-sided wind tower. Evaluated the transverse and longitudinal pitches of the heat recovery device. The proposed system performance was evaluated at different outdoor wind speed. CFD results indicated that the supply temperature can be raised up to 6.4 °C. The system satisfied the ventilation rate at the wind speed of 3 m/s and higher.